Bilabial V In Georgian Language According To Svanetian Manuscripts - Mikautadze, Maia (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
In scientific literature the qualification issue of the V sound is the matter of discussion in historic and in modern Georgian language as well. According to the one side of the scientists the dento-labial alphony of this sound is basic for Georgian speech (G. Akhvlediani, S. Jgenti, T. Gamkrelidze), for the second side of them - it is bilabial alphony (Iv. Kavtaradze, G.Rogava, T. Uturgaidze, T. Putkaradze). In this respect, the data of Svanetian lapidary recordings and historical documents are important. In case if the sources done with majuscule, miniscule and millitary alphabets the sixth letter-sign of the Georgian alphabet was the denoter of dento-labial V (and accordingly, this alphony is the basic for Georgian alphabet), it should have been presented in a seldom mode while fixing Svanetian verbal speech (in the language of epigraphs) due to the fact that for Svanetian language dento-labial Vini is strange. We have absolutely the different situation: in Svanetian manuscripts of different periods (IX-XVIII centuries) in CN-V, Cs-V, C-C, V-V, V-C positions, majuscule, miniscule and military images signifyinf V are presented with big frequency. That’s why dento-labial V sound is strange for Svanetian anguage, these images primarily were used to express bilabial sounds. Accordingly, the bilabial alphony in basic for the Georgian language.